EPIDEMIOLOGICAL OBSERVATORY: spreading of ESBL and carbapenemase positive strains in the period between January 2007 - June 2012, at the Hospital - University Campus - Hospital “Luigi Sacco” in Milan - Loredana Tocalli; Andrea Boselli; Sara Giordana Rimoldi; Maria Rita Gismondo (Microbiologia Medica, 2012)
Infections caused by ESBL-producing Enterobacteriaceae and carbapenemases producing bacteria are a growing phenomenon which is one of the leading causes of death among elderly or immunosuppressed patients and is also associated with a higher cost of hospitalization. As worldwide, also in Italy a steady and alarming increase of these microorganisms is reported. With the present paper we present a brief review of the prevalence of ESBL-producing and carbapenemase strains isolated at the Hospital - University Campus - Hospital “Luigi Sacco” in Milan between January 2007 and June 2012. Samples ESBLs positive (Vitek2: bioMérieux, France) were subjected to phenotype confirmation by E-test method (bioMérieux, France). In addition 34 K. pneumoniae carbapenemases producing strains collected between 2011 and 2012, were firstly confirmed with an Hodge test and then tested with a NASBA EasyQ KPCv1.0 test (bioMérieux, France) able to detect the bla KPC gene. The data collected showed a high prevalence of ESBLs and carbapenemases producing strains. 1828 out of 15585 were positive for ESBL with the following distribution: 15.6% E. coli, 13.0% K. pneumoniae, 3.6% Enterobacter spp, 7.7% P. mirabilis and 6% P. aeruginosa. Out of 1828, 193 samples (10.5%) were confirmed as positive and respectively 89.4% were E. Coli, 80% were K. pneumoniae and 89.5% were P. mirabilis. The 3.6% of strains were positive for carbapenemase: 45.3% were A. baumannii and 41.8% were P. aeruginosa. K. pneumoniae strains carbapenemase positive were confirmed in 100% of cases by the Hodge test and in 97% of cases by molecular investigation.